2013
DOI: 10.3354/ab00475
|View full text |Cite
|
Sign up to set email alerts
|

Estimating sex ratios in Caribbean hawksbill turtles: testosterone levels and climate effects

Abstract: Evolutionary theory predicts that male and female offspring should be produced at a 1:1 ratio, but this may rarely be the case for species in which sex is determined during incubation by temperature, such as marine turtles. Estimates of primary sex ratio suggest that marine turtle sex ratios are highly skewed, with up to 9 females per male. We captured juvenile hawksbill turtles Eretmochelys imbricata in waters around Anegada, British Virgin Islands, a regionally important foraging aggregation, and analysed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Hawksbill turtles were captured as part of an in-water sampling program using the rodeo technique (Limpus 1981) in waters around Anegada, British Virgin Islands (Fig. 1;(McGowan et al 2008;Hawkes et al 2013)). Surveys took place over 109 irregularly spaced days between the 16 November 2003 and the 8 August 2006, comprising a total effort of 543 h. Surveying for turtles took place in waters shallow enough for capture to take place (generally <20 m depth) and within the vicinity of reefs (see also (McGowan et al 2008;Witt et al 2010)).…”
Section: Turtle Capturementioning
confidence: 99%
See 1 more Smart Citation
“…Hawksbill turtles were captured as part of an in-water sampling program using the rodeo technique (Limpus 1981) in waters around Anegada, British Virgin Islands (Fig. 1;(McGowan et al 2008;Hawkes et al 2013)). Surveys took place over 109 irregularly spaced days between the 16 November 2003 and the 8 August 2006, comprising a total effort of 543 h. Surveying for turtles took place in waters shallow enough for capture to take place (generally <20 m depth) and within the vicinity of reefs (see also (McGowan et al 2008;Witt et al 2010)).…”
Section: Turtle Capturementioning
confidence: 99%
“…On occasions where curved carapace length (CCL) measurements were not collected (n = 26 turtles), they were estimated using straight carapace length (CCL = 1.1 9 SCL + 0.1; R 2 = 0.99, t = 171.0, P < 0.01 in 267 turtles for which we had both measurements), accepting that inaccuracies in the straight carapace length measurements would be carried forward to CCL estimates. Blood samples were collected from turtles for analysis of testosterone and oestradiol-17b (results reported in (Hawkes et al 2013)), and hormone values compared with thresholds reported in Geis et al (2003), Diez and van Dam (2003) and Blanvillain et al (2008) to estimate sex of captured individuals.…”
Section: Turtle Capturementioning
confidence: 99%
“…Because sea turtle eggs laid in the early and late nesting seasons are generally incubated under cool IT conditions (producing males) and warm IT conditions (producing females), respectively 41 53 , taken together, we suggest that hatchling survival rates during early life stages will differ by seasons as well as sexes. Such differences might account for why the sex ratio of juveniles is less female-biased than that of hatchlings in some populations 54 56 . Notably, sea turtles have survived many changes in climatic conditions over the past hundred million years 57 , suggesting that such sex differences of survival during early life stages might be one of the adaptive mechanisms to adjust the sex ratio at later life stages in response to changes in environmental condition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, equal hatchling sexes produced from the hatchery’s plot is very important for adult mating process in future when the turtle reaches maturity [approximately 20 years, Davenport (1997) ]. Evolutionary theory predicts that male and female offspring should be produced at a 1:1 ratio ( Hawkes et al . 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher incubation temperature (> 30°C) tends to produce more females while low incubation temperature (< 28°C) tends to produce more males ( Mrosovsky & Yntema 1980 ). This may be based on a mechanism known as temperature-dependent sex determination, TDS ( Hawkes et al . 2013 ) where equal sexes between males and females will be produced.…”
Section: Discussionmentioning
confidence: 99%